Block type polyaryl acridine anion exchange membrane and preparation method thereof
Through the design of the block polyaryl acridin anion exchange membrane, the polymer configuration and π-π stacking effect of acridin unit are used to solve the problem that the anion exchange membrane is difficult to balance with high ion conductivity and high dimensional stability, achieving high conductivity and good water swelling resistance, and improving the performance of the fuel cell.
Patent Information
- Application Number
- CN202411556700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
The problem of difficult balance between high ion conductivity and high dimensional stability of anion exchange membranes.
The block polyaryl acridin anion exchange membrane is adopted to control the microscopic phase separation morphology by changing the polymer configuration and introducing self-assembled acridinium units with π-π stacking effect, and promote efficient transmission of ions in the membrane.
It significantly improves the conductivity of the anion exchange membrane and maintains high water swelling resistance, improving its practical application performance in fuel cells.
Smart Images

Figure CN119518014A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange membranes, and in particular to a block-type polyarylacridine anion exchange membrane and a preparation method thereof. Background Art
[0002] Compared with traditional proton membrane fuel cells (PEMFCs), anion exchange membrane fuel cells (AEMFCs) are considered to be one of the most promising power generation technologies because they allow the use of non-precious metal electrode catalysts, which greatly reduces costs and has a low fuel leakage rate. As the core component of AEMFCs, anion exchange membranes (AEMs) can effectively block the anode and cathode and selectively transmit hydroxide ions. However, in the process of promoting the commercialization of AEMs, it is found that it still has certain limitations, which is mainly reflected in the problem that it is usually difficult to balance high ionic conductivity and high dimensional stability. Summary of the invention
[0003] The problem solved by the invention is how to solve the problem of the difficulty in balancing high ion conductivity and high dimensional stability of anion exchange membranes.
[0004] In order to solve the above problems, the present invention provides a block-type polyarylacridinium anion exchange membrane and a preparation method thereof.
[0005] In a first aspect, the present invention provides a block polyarylacridinium anion exchange membrane having a block configuration copolymer capable of achieving microphase separation, wherein the chemical formula of the block configuration copolymer is Formula 1:
[0006]
[0007] The block copolymer contains an acridine unit having a π-π conjugated structure, and the chemical formula of the acridine unit is Formula 2:
[0008]
[0009] In a second aspect, the present invention provides a method for preparing the block-type polyarylacridinium anion exchange membrane as described above, which specifically comprises the following steps:
[0010] S1: dissolving biphenyl and acridone in dichloromethane, then adding a super acid catalyst, stirring and reacting for more than 24 hours to obtain an oligomer;
[0011] S2: dissolving biphenyl and N-methyl-4-piperidone in dichloromethane, then adding a super acid catalyst dropwise, and continuously stirring the reaction for more than 40 minutes to obtain a viscous solution;
[0012] S3: adding the oligomer obtained in step S1 to the viscous solution in step S2, adding N-methyl-4-piperidone and a super acid catalyst, reacting for more than 4 hours to obtain a block copolymer solution, adding an ethanol solution for precipitation, filtering out the precipitate, and drying to obtain a block copolymer;
[0013] S4: dissolving the block copolymer obtained in step S3 in dimethyl sulfoxide, adding iodomethane and reacting in the dark at room temperature for more than 24 hours, then pouring into ethyl acetate for precipitation, filtering out the precipitate, and drying to obtain a quaternized block copolymer;
[0014] S5: dissolving the quaternized block copolymer obtained in step S4 in methyl sulfoxide to prepare a membrane solution, filtering and standing the obtained membrane solution for degassing, then pouring the obtained membrane solution onto a glass plate, and drying the membrane solution to obtain a block polyarylacridine anion exchange membrane.
[0015] Optionally, the super acid catalyst is trifluoromethanesulfonic acid or a mixture of trifluoromethanesulfonic acid and trifluoroacetic acid.
[0016] Optionally, the reaction temperature in step S1 is -20°C to -5°C.
[0017] Optionally, in step S2, a super acid catalyst is added dropwise at 0°C.
[0018] Optionally, the reaction temperature in step S3 is -10°C to -5°C.
[0019] Optionally, the precipitate obtained by precipitation of the ethanol solution in step S3 is washed with deionized water until it is neutral and then dried.
[0020] Optionally, the precipitate obtained by precipitation of ethyl acetate in step S4 is washed with deionized water and filtered, and placed in a vacuum drying oven at 60° C. for drying.
[0021] Alternatively, the membrane solution prepared in dimethyl sulfoxide is filtered through a polytetrafluoroethylene filter and then allowed to stand for degassing.
[0022] The beneficial effects of the block polyarylacridine anion exchange membrane and the preparation method thereof of the present invention are as follows: based on the regulation of microscopic phase separation morphology, by changing the polymer configuration, a block polyarylacridine anion exchange membrane is synthesized to construct a clearer microphase separation morphology, promote the efficient transmission of ions in the membrane, and thus significantly improve the conductivity of the anion exchange membrane; in addition, the acridine unit is a macrocyclic conjugated compound containing nitrogen elements, and the rigid planar conjugated structure is conducive to π-π stacking between molecules, enhancing the aggregation behavior of adjacent piperidine cations, and the anion exchange membrane provides an autonomous self-aggregation driving force through π-π interaction, thereby constructing By constructing continuous ion channels to further improve the conductivity, the block polymer configuration is designed and self-assembled acridine units with π-π stacking effect are introduced to achieve the coordinated regulation of the microscopic phase separation morphology by block structure and π-π self-assembly, thereby achieving the regulation of the microscopic phase separation morphology, macroscopic ionic conductivity and water swelling properties of the polyaryl anion exchange membrane, further confirming that the molecular structure of the anion exchange membrane plays a decisive role in the regulation of its microscopic morphology and macroscopic properties. The optimization at the microscopic level not only enhances the ionic conductivity and water swelling resistance of the anion exchange membrane, but also improves the actual application performance of the anion exchange membrane in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a synthetic route and structural schematic diagram of the block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) of this specific embodiment;
[0024] Figure 2 is a synthetic route of the random copolymerized poly(biphenyl-acridine-piperidine) polymer of this specific embodiment;
[0025] Figure 3 (a) is the H NMR spectrum of the block type poly(biphenyl-acridine-piperidine) polymer obtained in step (1) of Example 1, Example 2 and Example 3 and the random copolymerization type poly(biphenyl-acridine-piperidine) polymer in Comparative Example 1 ( 1 HNMR); Figure 3 (b) is the hydrogen nuclear magnetic resonance spectrum of the quaternized block type obtained in step (3) of Example 1, Example 2 and Example 3 and the quaternized polymer obtained in step (2) of Comparative Example 1 ( 1 HNMR);
[0026] Figure 4 is a differential scanning calorimetry (DSC) curve diagram of the polymers in Example 1, Example 2 and Example 3;
[0027] Figure 5 is a scanning electron microscope (SEM) image of the anion exchange membrane in Example 1, Example 2, Example 3 and Comparative Example 1;
[0028] Figure 6is a transmission electron microscope (TEM) image of the anion exchange membrane in Example 1, Example 2, Example 3 and Comparative Example 1;
[0029] Figure 7 is a graph showing the change of (a) water uptake (WU) and (b) swelling ratio (SR) of the anion exchange membrane in Example 1, Example 2, Example 3 and Comparative Example 1 with temperature;
[0030] Figure 8 The anion exchange membrane OH in Example 1, Example 2, Example 3 and Comparative Example 1 - Graph of conductivity versus temperature;
[0031] Fig. 9 It is a performance curve diagram of the anion exchange membrane H2 / O2 fuel cell in Example 2, Example 3 and Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0033] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by those skilled in the art to which this application belongs; the terms used in the specification of this application are only for the purpose of describing specific implementation methods and are not intended to limit this application;
[0034] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more.
[0035] In view of the problems existing in the above-mentioned related technologies, this embodiment provides a block-type polyarylacridinium anion exchange membrane and a preparation method thereof.
[0036] A block polyarylacridinium anion exchange membrane provided in an embodiment of the present invention has a block copolymer capable of achieving microphase separation, and the chemical formula of the block copolymer is Formula 1:
[0037]
[0038] The block copolymer contains a self-assembled acridine unit having a π-π conjugated structure, and the chemical formula of the self-assembled acridine unit is Formula 2:
[0039]
[0040] Specifically, x is the proportion of the acridine oligomer segment in the main chain, 1-x is the proportion of the piperidine segment in the main chain, and n is the degree of polymerization.
[0041] In this embodiment, based on the regulation of microscopic phase separation morphology, a block-type polyaryl acridine anion exchange membrane is synthesized by changing the polymer configuration to construct a clearer microphase separation morphology, promote efficient ion transmission in the membrane, and thus significantly improve the conductivity of the anion exchange membrane; in addition, the self-assembled acridine unit is a macrocyclic conjugated compound containing nitrogen elements, and the rigid planar conjugated structure is conducive to π-π stacking between molecules, enhancing the aggregation behavior of adjacent piperidine cations, and the anion exchange membrane provides an autonomous self-aggregation driving force through π-π interactions, thereby constructing a continuous ion channel to further improve the conductivity and maintain a high resistance to water swelling; the block configuration is designed and the self-assembled acridine unit with π-π stacking effect is introduced to achieve the coordinated regulation of the block structure and π-π self-assembly on the microscopic phase separation morphology, thereby achieving the regulation of the microscopic phase separation morphology of the polyaryl anion exchange membrane and the regulation of the macroscopic ionic conductivity and water swelling resistance, and improving its practical application performance in fuel cells. It was further confirmed that the molecular structure of anion exchange membrane plays a decisive role in regulating its micromorphology and macroscopic performance.
[0042] The present invention provides a method for preparing a block polyarylacridinium anion exchange membrane, which specifically comprises the following steps:
[0043] S1: dissolving biphenyl and acridone in dichloromethane, then adding a super acid catalyst, stirring and reacting for more than 24 hours to obtain an oligomer, wherein the oligomer is poly(biphenyl acridone) (PA);
[0044] S2: dissolving biphenyl and N-methyl-4-piperidone in dichloromethane, then adding a super acid catalyst dropwise, and continuously stirring and reacting for more than 40 minutes to obtain a viscous solution, wherein the viscous solution contains an oligomer poly(biphenyl-piperidone) (BMP);
[0045] S3: adding the oligomer obtained in step S1 to the viscous solution of step S2, adding N-methyl-4-piperidone and a super acid catalyst, reacting for more than 4 hours to obtain a block copolymer solution, adding an ethanol solution for precipitation, filtering out the precipitate, and drying to obtain a block copolymer, wherein the block copolymer is poly(biphenyl-acridine) block poly(biphenyl-piperidine) (PA-b-BMP);
[0046] S4: dissolving the block copolymer obtained in step S3 in dimethyl sulfoxide, adding iodomethane and reacting at room temperature in the dark for more than 24 hours, then pouring into ethyl acetate for precipitation, filtering out the precipitate, and drying to obtain a quaternized block copolymer, wherein the quaternized block copolymer is a quaternized poly(biphenyl-acridine) block poly(biphenyl-piperidine) (QPA-b-BMP);
[0047] S5: dissolving the quaternized block copolymer obtained in step S4 in dimethyl sulfoxide to prepare a membrane solution, standing to degas, pouring the obtained membrane solution onto a glass plate, and drying to obtain a block polyarylacridine anion exchange membrane.
[0048] In this embodiment, based on the regulation of microscopic phase separation morphology, a block polyaryl acridine anion exchange membrane is synthesized by changing the polymer configuration to construct a clearer microphase separation morphology, promote efficient ion transport in the membrane, and thus significantly improve the conductivity of the anion exchange membrane; in addition, the acridine unit is a macrocyclic conjugated compound containing nitrogen elements, and the rigid planar conjugated structure is conducive to π-π stacking between molecules, enhancing the aggregation behavior of adjacent piperidine cations, and the anion exchange membrane provides an autonomous self-aggregation driving force through π-π interactions, thereby constructing a continuous ion channel to further improve the conductivity; a block polyaryl acridine anion exchange membrane containing acridine units is prepared to achieve the coordinated regulation of the block configuration and π-π self-assembly on the microscopic self-assembly morphology of the membrane, thereby achieving the regulation of the microscopic phase separation morphology and macroscopic ionic conductivity and water swelling properties of the polyaryl anion exchange membrane, so as to prepare an anion exchange membrane with high ionic conductivity.
[0049] Specifically, Figure 1 As shown, S1 is Figure 1 The chemical formula of the second line in the formula is: Figure 1 The chemical formula of the first line in the formula is used to obtain a viscous solution BMP. S3 is the chemical formula of the copolymerization of the viscous solution in the first line with the oligomer poly(biphenyl acridine) polyamide block in the second line to obtain a block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) PA-b-BMP-x. Where x represents the proportion of the acridine oligomer segment in the polymer main chain: x = 0.10, 0.20, and correspondingly, 1-x is the proportion of the piperidine segment in the main chain, 1-x = 0.90, 0.80.
[0050] S4 Figure 1 The chemical formula in the third row of the formula gives the quaternized block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) QPA-b-BMP-x.
[0051] Optionally, the super acid catalyst is trifluoromethanesulfonic acid or a mixture of trifluoromethanesulfonic acid and trifluoroacetic acid.
[0052] In this optional embodiment, the super acid acts as a good catalyst, allowing some reactions that are difficult to carry out to be carried out under milder conditions, thereby simplifying the operation and reducing the operating cost.
[0053] Optionally, the reaction temperature in step S1 is -20°C to -5°C.
[0054] In this optional embodiment, at a temperature of -20°C to -5°C, a super acid catalyst is added, and the reaction is terminated after stirring for 24 hours. The obtained viscous dark green solution is poured into an aqueous solution to obtain a yellow powder product.
[0055] Optionally, in step S2, a super acid catalyst is added dropwise at 0°C.
[0056] In this optional embodiment, at a temperature of 0°C, after reacting for 40 minutes, the solution becomes light red and viscous.
[0057] Optionally, the reaction temperature in step S3 is -10°C to -5°C.
[0058] In this optional embodiment, the temperature is reduced from 0°C to -10°C to -5°C, and a viscous reaction solution is obtained, which is poured into an ethanol solution for precipitation to obtain a yellow fibrous product.
[0059] Optionally, the precipitate obtained by precipitation of the ethanol solution in step S3 is washed with deionized water until it is neutral and then dried.
[0060] In this optional embodiment, the precipitate is washed with deionized water, which can remove both the unreacted reactants and the ethanol solution without impurities.
[0061] Optionally, the precipitate obtained by precipitation of ethyl acetate in step S4 is washed with deionized water and filtered, and placed in a vacuum drying oven at 60° C. for drying.
[0062] In this optional embodiment, the precipitate is washed with deionized water to remove unreacted reactants and ethyl acetate without impurities; it is dried in a vacuum drying oven at 60°C to achieve rapid drying, and no further reaction occurs under the vacuum environment.
[0063] Alternatively, the membrane solution prepared in dimethyl sulfoxide is filtered through a polytetrafluoroethylene filter and then allowed to stand for degassing.
[0064] In this optional embodiment, the polytetrafluoroethylene filter has a high filtration accuracy. The filtration accuracy of the polytetrafluoroethylene filter element is generally between 0.1-10 microns, which can remove smaller particles and microorganisms and provide a higher filtration effect.
[0065] The present invention is further described below in conjunction with specific embodiments.
[0066] Example 1
[0067] A method for preparing a block poly (biphenyl-acridine) block poly (biphenyl-piperidine) QPA-b-BMP-5 anion exchange membrane, the steps of which are as follows:
[0068] (1) Synthesis of oligomeric poly(biphenylacridine) PA: Biphenyl (0.771 g) and acridone (1.37 g) were dissolved in dichloromethane (6.6 mL), and trifluoroacetic acid (0.56 mL) and trifluoromethanesulfonic acid (6.6 mL) were added in a low-temperature reactor at -10°C. The mixture was stirred and reacted at low temperature for 24 hours. After the reaction, the viscous dark green solution was poured into an aqueous solution to obtain a yellow powdery product. The product was filtered, washed with deionized water until neutral, and dried to obtain oligomeric poly(biphenylacridine) PA.
[0069] (2) Synthesis of block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) (PA-b-BMP-5): First, biphenyl (0.15 g) and N-methyl-4-piperidone (143 μL) were dissolved in dichloromethane (0.88 mL), and trifluoroacetic acid (74 μL) and trifluoromethanesulfonic acid (0.88 mL) were added dropwise at 0°C. The mixture was stirred for 40 minutes. When the solution was light red and viscous, oligomer poly(biphenylacridine) PA (0.017 g) was added, and N-methyl-4-piperidone (60 μL) and trifluoromethanesulfonic acid (0.88 mL) were added. The temperature was then lowered to -10°C. After 4 hours, a viscous reaction solution was obtained. The solution was poured into an ethanol solution for precipitation to obtain a yellow fibrous product. The product was washed with deionized water until neutral and dried to obtain the block copolymer PA-b-BMP-5.
[0070] (3) Synthesis of quaternary ammonium block copolymer QPA-b-BMP-5: PA-b-BMP-5 (1.0 g) was dissolved in dimethyl sulfoxide (20 mL), and iodomethane (350 μL) was added. The mixture was reacted at room temperature in the dark for 24 h to obtain an orange-red solution, which was poured into ethyl acetate to precipitate a yellow fibrous solid. The solid was washed with deionized water, filtered, and placed in a vacuum drying oven at 60°C and dried overnight to obtain a quaternary ammonium block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) QPA-b-BMP-5.
[0071] (4) Preparation of block poly(biphenyl-acridine) block poly(biphenyl-piperidine) anion exchange membrane (QPA-b-BMP-5): QPA-b-BMP-5 (0.5 g) was dissolved in dimethyl sulfoxide (10 mL) to prepare a 5 wt % membrane solution, which was filtered through a 0.45 μm polytetrafluoroethylene filter and allowed to stand for degassing. The resulting membrane solution was poured onto a clean, flat glass plate and dried on a hot plate at 80° C. to obtain an anion exchange membrane.
[0072] Example 2
[0073] A method for preparing a block poly (biphenyl-acridine) block poly (biphenyl-piperidine) QPA-b-BMP-10 anion exchange membrane, the steps of which are as follows:
[0074] (2) Synthesis of block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) (PA-b-BMP-10): First, biphenyl (0.15 g) and N-methyl-4-piperidone (143 μL) were dissolved in dichloromethane (0.88 mL), and trifluoroacetic acid (74 μL) and trifluoromethanesulfonic acid (0.88 mL) were added dropwise at 0°C. The mixture was stirred for 40 minutes. When the solution was light red and viscous, oligomer poly(biphenyl-acridine) PA (0.033 g) was added, and N-methyl-4-piperidone (60 μL) and trifluoromethanesulfonic acid (0.88 mL) were added. The temperature was then lowered to -10°C. After 4 hours, a viscous reaction solution was obtained. The solution was poured into an ethanol solution for precipitation to obtain a yellow fibrous product. The product was washed with deionized water until neutral and dried to obtain the block copolymer PA-b-BMP-10.
[0075] The methods of step (1), step (3) and step (4) are the same as those of Example 1, except that in step (2), an amount of oligomer poly(biphenyl acridine) PA is added to obtain a block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) QPA-b-BMP-10 anion exchange membrane.
[0076] Example 3
[0077] A method for preparing a block poly (biphenyl-acridine) block poly (biphenyl-piperidine) QPA-b-BMP-20 anion exchange membrane, the steps of which are as follows:
[0078] (2) Synthesis of block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) (PA-b-BMP-20): First, biphenyl (0.15 g) and N-methyl-4-piperidone (143 μL) were dissolved in dichloromethane (0.88 mL), and trifluoroacetic acid (74 μL) and trifluoromethanesulfonic acid (0.88 mL) were added dropwise at 0°C. The mixture was stirred for 40 minutes. When the solution was light red and viscous, oligomer poly(biphenyl-acridine) PA (0.066 g) was added, and N-methyl-4-piperidone (60 μL) and trifluoromethanesulfonic acid (0.88 mL) were added. The temperature was then lowered to -10°C. After 4 hours, a viscous reaction solution was obtained. The solution was poured into an ethanol solution for precipitation to obtain a yellow fibrous product. The product was washed with deionized water until neutral and dried to obtain the block copolymer PA-b-BMP-20.
[0079] The methods of step (1), step (3) and step (4) are the same as those of Example 1, except that in step (2), an amount of oligomer poly(biphenyl acridine) PA is added to obtain a block copolymer poly(biphenyl-acridine) block poly(biphenyl-piperidine) QPA-b-BMP-20 anion exchange membrane.
[0080] Comparative Example 1
[0081] A method for preparing a random copolymer poly (biphenyl-acridine-piperidine) QPABMP-10 anion exchange membrane, such as Figure 2 As shown, the steps are as follows:
[0082] (1) Synthesis of poly(biphenyl-acridine-piperidine) polymer PABMP-10: Biphenyl (0.154 g), acridone (0.027 g) and N-methyl-4-piperidone (141 μL) were dissolved in dichloromethane (1.2 mL), trifluoroacetic acid (104 μL) and trifluoromethanesulfonic acid (1.24 mL) were added in a low temperature reactor at -10°C, and stirred for 12 hours at low temperature. After the reaction, a viscous dark green solution was obtained. The product was slowly poured into a 1M NaOH solution for precipitation to obtain a light yellow fibrous product, which was washed with deionized water until neutral and dried to obtain poly(biphenyl-acridine-piperidine) copolymer PABMP-10. The proportion of acridine in the polymer backbone was adjusted by adjusting the feed ratio of acridone to piperidine.
[0083] The methods of step (2) and step (3) are the same as those of step (3) and step (4) of Example 1, except that iodomethane (430 μL) is added in step (3) to prepare a random copolymer poly(biphenyl-acridine-piperidine) QPABMP-10 anion exchange membrane.
[0084] Figure 3 (a) are the nuclear magnetic resonance hydrogen spectra of the polymers PA-b-BMP-5, PA-b-BMP-10, PA-b-BMP-20 and PABMP-10 obtained in step (1) of Example 1, Example 2, Example 3 and Comparative Example 1, respectively. The phenyl protons show significant resonance peaks in the nuclear magnetic resonance spectrum, which appear between chemical shifts of 7.0-8.0 ppm, corresponding to peaks a and b in the figure; in addition, the methyl hydrogen on the piperidine ring is affected by the protonation of trifluoroacetic acid, splitting occurs, generating peaks c and d, which are between 2.0-2.8 ppm and 2.8-3.1 ppm, respectively; the chemical shift of the methyl hydrogen on the piperidine ring is 2.75 ppm, corresponding to peak e on the nuclear magnetic resonance spectrum. With the increase of the molar ratio of the acridine segment, the integrated area of the protons in the aromatic region gradually increases. Through the integrated area ratio of the characteristic peak c on the piperidine ring and the peak in the aromatic region, it can be found that the actual reaction percentage of acridone is almost consistent with the feed ratio. The above proves that the polymers PA-b-BMP-5, PA-b-BMP-10, PA-b-BMP-20 and PABMP-10 were successfully synthesized. Figure 3(b) are hydrogen nuclear magnetic resonance spectra of the polymers QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 obtained in step (3) of Example 1, Example 2 and Example 3 and step (2) of Comparative Example 1, respectively. It can be seen that the shift of the quaternized polymer is very similar to the chemical shift of the precursor, except that the methylene proton peak on the piperidine ring disappears after quaternization, accompanied by the migration of the methyl peak e on the piperidine ring from 2.77 ppm to 3.16 ppm, which proves the successful quaternization of the polymer.
[0085] Figure 4 The glass transition temperatures Tg of the polymers PA-b-BMP-5, PA-b-BMP-10 and PA-b-BMP-20 prepared in step (1) of Example 1, Example 2 and Example 3 were measured by differential scanning calorimetry (DSC). The Tg values of PA-b-BMP-5, PA-b-BMP-10 and PA-b-BMP-20 had only one peak, which further supported the formation of block polymers. As the molar ratio of acridine increased, Tg increased, which was caused by the acridine unit with greater rigidity.
[0086] Figure 5 Scanning electron microscope images (SEM) of anion exchange membranes QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 prepared in step (1) of Example 1, Example 2, Example 3 and Comparative Example 1, respectively; Figure 5 (ad) are the surface images of the films QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10. It can be seen from the figure that the series of films all present a dense and uniform morphology; Figure 5 (eh) It can be seen that the cross-sectional morphologies of the membranes QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 are similar. Except for the difference in film thickness, there are no obvious defects, indicating that the membranes have good air tightness and can effectively block the penetration of fuel.
[0087] Figure 6The transmission electron microscope images (TEM) of the anion exchange membranes QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 prepared in step (1) of Example 1, Example 2, Example 3 and Comparative Example 1 are respectively shown; the ion transport channels formed by the anion exchange membrane QPABMP-10 are not as clear and obvious as those of the block membranes QPA-b-BMP-10 and QPA-b-BMP-20, and this difference further confirms the effectiveness of the block structure in improving the performance of the membrane material. Specifically, the block structure can effectively break the chain stacking interlocking phenomenon between polymer molecules, utilize the thermodynamic incompatibility of the hydrophilic segment and the hydrophobic segment, promote the orderly self-assembly of the polymer chain during the film formation process, and form a clearer microscopic phase separation and interpenetrating ion domains, among which the microscopic phase separation of the block membrane QPA-b-BMP-10 with a content of 10% is the most obvious, and the hydrophilic region has better interpenetration.
[0088] Figure 7 The water uptake (WU) and swelling ratio (SR) curves of the anion exchange membranes QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 obtained in step (1) of Example 1, Example 2, Example 3 and Comparative Example 1 respectively vary with temperature. As the temperature increases, the thermal motion of the molecules intensifies, thereby increasing the water content in the membrane accordingly. Comparing the water content of the random membrane QPABMP-10 and the block membrane QPA-b-BMP-10, which have substantially the same acridine content ratio but significantly different main chain structures, it is found that the WU of the block AEMs is higher, whether at room temperature or at high temperature; for example, at 80°C, the WU of QPABMP-10 is 89%, while the WU of QPA-b-BMP-10 is 96%. This difference indicates that the presence of the block structure enhances the water absorption capacity of AEMs to a certain extent, but still maintains a low water swelling property. For example, the SR of the membrane QPA-b-BMP-10 at 80°C is 41.1%, which is comparable to the SR of QPABMP-10 (38.5%), indicating that the block polyarylacridine membrane can maintain good water swelling resistance while increasing the water absorption capacity. Generally speaking, a higher water absorption capacity can promote the transport of hydroxide ions and improve ionic conductivity.
[0089] Figure 8 The OH groups of the anion exchange membranes QPA-b-BMP-5, QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 prepared in step (1) of Example 1, Example 2, Example 3 and Comparative Example 1 are shown in FIG. -The curve of conductivity changing with temperature; it is obvious from the figure that the OH - The conductivity shows a trend of increasing significantly with increasing temperature, which is because the increase in temperature promotes the thermal motion between water molecules, thereby accelerating the ion mobility. The ionic conductivity of the QPA-b-BMP-10 membrane reaches a maximum of 176.65 mS cm at 80 °C. -1 The ionic conductivity of QPA-b-BMP-20 membrane reached 163.31 mS cm -1 , compared with the anion exchange membrane QPABMP-10 conductivity of 155.11mS cm -1 , block AEMs have a significant improvement in conductivity. This is because the block structure and the π-π stacking between acridine units synergistically induce the orderly self-assembly between chains. At the same time, the interaction between cations and hydrophobic skeletons forms a significant difference in hydrophilicity / hydrophobicity, forming an ideal hydrophilic / hydrophobic microphase separation structure inside the membrane, which is conducive to the improvement of conductivity.
[0090] Fig. 9 The H2 / O2 fuel cell performance of the anion exchange membranes QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 prepared in step (1) of Example 2, Example 3 and Comparative Example 1, respectively; it can be seen from the figure that the open circuit voltages of the anion exchange membranes QPA-b-BMP-10, QPA-b-BMP-20 and QPABMP-10 are all around 1.0V, indicating good gas barrier properties. The maximum peak power density of QPA-b-BMP-10 and QPA-b-BMP-20 membranes is 687mW cm -2 and 556 mW cm -2 Compared with the random copolymer QPABMP-10, the peak power density is 240 mW cm -2 The block QPA-b-BMP-10 and QPA-b-BMP-20 membranes have greatly improved the battery performance, further demonstrating the potential of block polyarylacridinium AEMs in fuel cell applications.
[0091] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A block polyarylacridine anion exchange membrane, characterized in that ,, having a block configuration copolymer capable of achieving microphase separation, the chemical formula of the block configuration copolymer is Formula 1: The block copolymer contains an acridine unit having a π-π conjugated structure, and the chemical formula of the acridine unit is Formula 2:
2. A method for preparing a block polyarylacridinium anion exchange membrane as claimed in claim 1, characterized in that: The specific steps include: S1: dissolving biphenyl and acridone in dichloromethane, then adding a super acid catalyst, stirring and reacting for more than 24 hours to obtain an oligomer; S2: dissolving biphenyl and N-methyl-4-piperidone in dichloromethane, then adding a superacid catalyst dropwise, and continuously stirring the reaction for more than 40 minutes to obtain a viscous solution; S3: adding the oligomer obtained in step S1 to the viscous solution in step S2, adding N-methyl-4-piperidone and a super acid catalyst, reacting for more than 4 hours to obtain a block copolymer solution, adding an ethanol solution for precipitation, filtering out the precipitate, and drying to obtain a block copolymer; S4: dissolving the block copolymer obtained in step S3 in dimethyl sulfoxide, adding iodomethane, reacting at room temperature in the dark for more than 24 hours, then pouring into ethyl acetate for precipitation, filtering out the precipitate, and drying to obtain a quaternized block copolymer; S5: dissolving the quaternized block copolymer obtained in step S4 in dimethyl sulfoxide to prepare a membrane solution, filtering and standing the obtained membrane solution for degassing, then pouring the obtained membrane solution onto a glass plate, and drying the obtained membrane solution to obtain a block polyarylacridine anion exchange membrane.
3. The method for preparing a block-type polyarylacridinium anion exchange membrane according to claim 2, characterized in that: The super acid catalyst is trifluoromethanesulfonic acid or a mixture of trifluoromethanesulfonic acid and trifluoroacetic acid.
4. The method for preparing a block-type polyarylacridinium anion exchange membrane according to claim 2, characterized in that: The reaction temperature in step S1 is -20°C to -5°C.
5. The method for preparing a block-type polyarylacridinium anion exchange membrane according to claim 2, characterized in that: In step S2, the super acid catalyst is added dropwise at 0°C.
6. The method for preparing a block polyarylacridinium anion exchange membrane according to claim 2, characterized in that: The reaction temperature in step S3 is -10°C to -5°C.
7. The method for preparing a block polyarylacridinium anion exchange membrane according to claim 2, characterized in that: The precipitate obtained by precipitation of the ethanol solution in step S3 is washed with deionized water until it becomes neutral and then dried.
8. The method for preparing a block polyarylacridinium anion exchange membrane according to claim 2, characterized in that: The precipitate obtained by precipitation of ethyl acetate in step S4 is washed with deionized water and filtered, and placed in a vacuum drying oven at 60° C. for drying.
9. The method for preparing a block polyarylacridinium anion exchange membrane according to claim 2, characterized in that: The membrane solution prepared in dimethyl sulfoxide was filtered through a polytetrafluoroethylene filter and then allowed to stand for degassing.